Retrieving and recontextualising VET theory (Themenheft) - Esmond, Bill [Verfasser]; Wedekind, Volker [Verfasser]; Gonon, Philipp [Verfasser]; Bonoli, Lorenzo [Verfasser]; Ketschau, Thilo [Verfasser]; Kutscha, Günter [Verfasser]; Stomporowski, Stephan [Verfasser]; Slopinski, Andreas [Verfasser]; Steib, Christian [Verfasser]; Hinchliffe, Geoffrey [Verfasser]; Alphonsus, Naomi S. [Verfasser]; Li, Junmin [Verfasser]; et al. (My University, 2023)
„The COVID-19 pandemic and the climate emergency have drawn attention to the vulnerability of our way of life and VET’s responsibilities for its foundations. At the same time, the rise of populist and far-right political currents in older industrialised countries implies that any form of education and upbringing still has to address urgent questions about the purposes and aims of education. Further developments, such as digitisation and automation, now advancing in many areas of life, need to be further examined in terms of their implications for educational theory and philosophy. Against this background, we review the way these ideas have been shaped by the previous genesis of vocational education and training (VET) formation and the shaping of individual theories – either reflected in the context of their historicity (retrieval) or in the context of their topicality (recontextualisation). Furthermore, these retrieving and recontextualising horizons are not only intended to illustrate the current status and perspectives of these theories, but also to provide possibilities for the further development of methodological approaches and theories in VET. Fundamental to the concern to publish a paper with a focus on educational theory in the field of VET is the question of why a discipline that is currently strongly characterised by empiricism and practical relevance should address such concerns. […] In presenting Special Issue (SI) 19, it is necessary to clarify what is to be understood by its actual object of discussion, VET theory.“ (excerpt; BIBB-Doku)
Keywords: T Theorieentwicklung & Methodologie; 370; 300; Berufsbildung; Berufsbildungstheorie; Definition; Emanzipation; Nachhaltige Entwicklung; Ökologie; Ethik; Lerntheorie; Kompetenz; Begriff; Internationale Zusammenarbeit; Verkäufer; Kaufmann im Einzelhandel; Berufsbildposition; Beruflichkeit; Vereinigtes Königreich; Schweiz; Bundesrepublik Deutschland; Norwegen